Penerapan Aplikasi Samsat Digital sebagai Layanan Publik di Sumatera Selatan - Dedek Kurniadi; Tata Sutabri (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
The Samsat Digital application is designed to improve efficiency and transparency in the management of motor vehicle taxes in South Sumatra. The main goal is to provide the best service to the public using information technology. The Samsat Digital application is an innovative solution that aims to make it easier for the public to access motor vehicle tax administration services. This application provides various features that allow users to make vehicle tax payments, check tax status, extend STNK, and search for information related to Samsat services online. Through mobile application-based technology, Samsat Digital seeks to reduce long queues at Samsat offices, increase time efficiency, and provide a more practical user experience. This system is equipped with secure authentication features, tax payment reminder notifications, and integration with various digital payment methods such as e-wallets, mobile banking, and credit cards.Keyword : Aplikasi Samsat Digital.